Patients' Perception of Missed Nursing Care in a Tertiary Hospital: A Cross‐Sectional Study - Afia Achiaa Sarpong; Amanda Towell‐Barnard; Lucy Gent; Ebenezer Afrifa‐Yamoah; Diana Arabiat (Nursing Open)
ABSTRACT Aims To identify types of patient‐reported missed nursing care and adverse events and identify the factor associated with missed care in a Western Australian tertiary hospital. Background Research in the domain of missed nursing care has established the association between missed nursing care and unsafe patient outcomes. However, there is a paucity of evidence on patient perception of missed nursing care and associated factors. Design Cross‐sectional study. Method A study of inpatients in a tertiary teaching hospital in Western Australia was carried out. Ninety‐eight patients admitted in 16 medical and surgical wards were sampled. The patient MISSCARE survey was used to capture patient‐reported types of missed care, prevalence of adverse events and the association between missed care, unit type, demographic characteristics and patient health problems. Descriptive and logistic analysis were performed using SPSS. Findings The most frequently reported missed nursing care activities included mouth care (63%), ambulation (35%), helping patient out of bed into a chair (31%), informing patient about tests or procedures (29%) and considering patient opinion (27%). The majority of reported missed care activities were from basic care domain followed by communication. The most common adverse events reported were intravenous infusion leaking into skin, intravenous fluid running dry, falls and development of pressure ulcer. Significant association was observed between missed nursing care and patient age. Discussion The findings of this study showed significant level of patient‐reported missed nursing care particularly in the domain of basic care. Although this study's limitations, including its small sample size and potential response bias, warrant caution in generalising the findings, the insights gained provide a valuable foundation for future research aimed at improving patient care. Conclusion Findings provide valuable insight about patient's perception of missed care and inform the need for effective interventions to reduce unsafe outcomes related to missed nursing care. Relevance to Clinical Practice Healthcare systems need to make necessary efforts to ensure that patients receive the right amount of care needed to maintain and promote safe hospitalisation outcomes. Reporting Method The study was reported according to the STROBE guidelines. Patient or Public Contribution The development of this study protocol, data collection, analysis and interpretation of results were carried out through a collaborative effort between patients, families and the research team.